PROGNOSTIC SIGNIFICANCE OF CAROTID INTIMA-MEDIA THICKNESS IN THE ASSESSMENT OF CORONARY ARTERY ATHEROSCLEROSIS - Parmonova Nazokat Abdisodik kizi (Modern American Journals, 2025)
Atherosclerosis is a progressive, chronic inflammatory disease that affects large and medium-sized arteries throughout the body. It is the underlying cause of major cardiovascular events such as myocardial infarction, stroke, and peripheral artery disease, contributing to the majority of cardiovascular mortality worldwide. The early detection of subclinical atherosclerosis has therefore become a crucial component of preventive cardiology.
Keywords: Carotid artery, intima-media thickness, coronary atherosclerosis, cardiovascular risk, ultrasound, non-invasive diagnostics.